Block-diagonal reduction of matrices over an n-simple Bézout domain (n ≥ 3) - Domsha, O.V.; Zabavskii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
It is known that a simple Bézout domain is the domain of elementary divisors if and only if it is 2-simple. The block-diagonal reduction of matrices over an n -simple Bézout domain (n ≥ 3) is realized.